2001
DOI: 10.1177/002246690103500201
|View full text |Cite
|
Sign up to set email alerts
|

Is the Glass Half Full or Half Empty?

Abstract: Help Wanted: Individuals who are enthusiastic, intelligent, energetic, and personable to work in challenging situations with challenging individuals. Extrinsic rewards minimal. Intrinsic rewards unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Causton-Theoharis et al (2007) and Mastropieri (2001) report that collaborating with other adults is one of the major challenges faced by first-year teachers. Calder and Grieve (2004) suggest some reasons why teachers lack skills in this area.…”
Section: Training For Teachersmentioning
confidence: 99%
“…Causton-Theoharis et al (2007) and Mastropieri (2001) report that collaborating with other adults is one of the major challenges faced by first-year teachers. Calder and Grieve (2004) suggest some reasons why teachers lack skills in this area.…”
Section: Training For Teachersmentioning
confidence: 99%
“…Additionally, professional development provided by districts can be quite limited. As a result, many teachers feel poorly prepared to lead paraprofessionals and indicate they need more support in this area (Berry, Petrin, Gravelle, & Farmer, 2011; Mastropieri, 2001).…”
mentioning
confidence: 99%
“…On the other hand, previous studies have found several factors that can affect the level of job satisfaction experienced by teachers, such as the overall school environment, access to resources, and the manageability of workload. In addition, the level of school support perceived by a teacher directly affects job satisfaction (Mastropieri, 2001;Prather-Jones, 2011). As can be seen, previous studies generally emphasize the effect of classroom management and school climate on job satisfaction.…”
Section: The Mediating Roles Of Loneliness At Work and Burnout In The...mentioning
confidence: 99%